The Biochemical Mechanisms of Antimicrobial Photodynamic Therapy. (12th August 2022) - Sabino, Caetano P.; Ribeiro, Martha S.; Wainwright, Mark; dos Anjos, Carolina; Sellera, Fábio P.; Dropa, Milena; Nunes, Nathalia B.; Brancini, Guilherme T. P.; Braga, Gilberto U. L.; Arana‐Chavez, Victor E.; Freitas, Raul O.; Lincopan, Nilton; et al.
Abstract: The unbridled dissemination of multidrug‐resistant pathogens is a major threat to global health and urgently demands novel therapeutic alternatives. Antimicrobial photodynamic therapy (aPDT) has been developed as a promising approach to treat localized infections regardless of drug resistance profile or taxonomy. Even though this technique has been known for more than a century, discussions and speculations regarding the biochemical mechanisms of microbial inactivation have never reached a consensus on what is the primary cause of cell death. Since photochemically generated oxidants promote ubiquitous reactions with various biomolecules, researchers simply assumed that all cellular structures are equally damaged. In this study, biochemical, molecular, biological and advanced microscopy techniques were employed to investigate whether protein, membrane or DNA damage correlates better with dose‐dependent microbial inactivation kinetics. We showed that although mild membrane permeabilization and late DNA damage occur, no correlation with inactivation kinetics was found. On the other hand, protein degradation was analyzed by three different methods and showed a dose‐dependent trend that matches microbial inactivation kinetics. Our results provide a deeper mechanistic understanding of aPDT that can guide the scientific community toward the development of optimized photosensitizing drugs and also rationally propose synergistic combinations with antimicrobial chemotherapy. Abstract : Microbial drug resistance emerged as a critical challenge for human and animal health worldwide, emphasizing the need for disrupting antimicrobial strategies. Antimicrobial photodynamic therapy (aPDT) has the potential to overcome drug‐resistant infections because it does not rely on specific targets. Herein, we investigated the microbial inactivation kinetics promoted by aPDT alongside the molecular damage caused to cell membrane, DNA, and proteins of Klebsiella pneumoniae . We concluded that bacterial cell death is closely associated with protein degradation while the membrane and DNA damages are secondary effects. Such knowledge indicates the most effective pathways for the development of optimized therapeutic protocols.